Measuring of the Genotoxic and Potential Antioxidant Effects of Essential Oil Obtained from Satureja Hortensis Against to Phaseolus Vulgaris - Bozari, Sedat (INST TECNOLOGIA PARANA, 2016)
It is known that, there are many ways for increasing the yield at the crops specially cereal products. Genetic manipulations and physiological interventions are the primary studies that aim to obtain products at high quality and amounts. It is known that, the usage of synthetic chemicals for physiological inverventions negatively affects organism. But using natural plant products instead of these chemicals is a subject that draws attention of today scientific environment. In this study, this situation was taken into consideration and the essential oil obtained from Satureja hortensis (SEO) plant were applied to bean seeds. The genotoxic and physiological effects of SEO at four different dosages were detected against to Phaseolus vulgaris seedlings. According to obtained data, essential oil that were applied at different doses decreased the genomic stability of the bean seeds up to 30.77% in accordance with the increased dosage. The essential oil applied in the same way lead to stress on enzyme activities of seedlings. Among the antioxidant enzymes, while, significant changeswere observed at Superoxide dismutase and Peroxidase enzymes according to the control, no significant change was seen at Ascorbate peroxidase level.
Keywords: Antioxidant Enzymes; Biyopesticide; Essential Oil; GTS